2013
DOI: 10.1155/2013/151807
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Insecticide Methamidophos Suppressed Production of Proinflammatory Cytokines Responding to Virus Infection in Lung Tissues in Mice

Abstract: Methamidophos, a representative organophosphate insecticide, is regulated because of its severe neurotoxicity, but it is suspected of contaminating agricultural foods in many countries due to illicit use. To reveal unknown effects of methamidophos on human health, we evaluated the developmental immunotoxicity of methamidophos using a respiratory syncytial virus (RSV) infection mouse model. Pregnant mice were exposed to methamidophos (10 or 20 ppm) in their drinking water from gestation day 10 to weaning on pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…51 On the other hand, mice exposed to methamidophos in drinking water from gestation day 10 to postnatal day 21 had lower levels of IL-6 following infection with respiratory syncytial virus. 52 However, on the whole, there is a paucity of laboratory data that have examined the relationship between pesticides and lung health.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…51 On the other hand, mice exposed to methamidophos in drinking water from gestation day 10 to postnatal day 21 had lower levels of IL-6 following infection with respiratory syncytial virus. 52 However, on the whole, there is a paucity of laboratory data that have examined the relationship between pesticides and lung health.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One study found no difference in the extent of LPS-induced lung inflammation following 90-day oral exposures of mice to ethion (an OP insecticide) and vehicle . On the other hand, mice exposed to methamidophos in drinking water from gestation day 10 to postnatal day 21 had lower levels of IL-6 following infection with respiratory syncytial virus . However, on the whole, there is a paucity of laboratory data that have examined the relationship between pesticides and lung health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal exposure to methamidophos interferes with neutrophil recruitment through IL-6 and interferon in response to the respiratory syncytial virus (RSV) in the lung tissue in the offspring generation of mice [ 99 ]. In addition, 2,2-Dichlorovinyl dimethyl phosphate (DDVP) induced inhibition of NK, limphokine-activated killer cells (LAK), and Cytotoxic T lymphocytes (CTL) activities in KO mice, through the impairment of the FasL/Fas pathway-associated phenomenon [ 100 ].…”
Section: Op-mediated Modulation Of the Immune Responsementioning
confidence: 99%
“…To evaluate the immunotoxicity of environmental chemicals including BFRs, we established a novel assay system using a murine model of RSV infection because the severity of RSV infection reflects the condition of the host immunity (Watanabe et al, 2008a). We subsequently demonstrated that decabrominated diphenyl ether (DBDE), a BFR, and methamidophos, a representative organophosphate insecticide, caused developmental immunotoxicity (Watanabe et al, 2008b) and suppressed the production of proinflammatory cytokines using this model (Watanabe et al, 2013), respectively. In addition, we also revealed that titanium dioxide caused immune disorder and then exacerbated pneumonia in RSV-infected mice (Hashiguchi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%